Das pinturas aos contos: uma proposta de escrita para alunos do 7º ano do ensino fundamental - Lessa, David Perdigão (2025)
In the context of writing instruction, it is essential to acknowledge the importance of diversifying pedagogical practices to stimulate students’ creativity. Prompted by the observation that creative writing is scarcely valued in educational settings, this work, entitled “From Paintings to Short Stories: A Writing Proposal for 7th-Grade Elementary School Students,” investigates the interaction between writing practice and image reading, focusing on the paintings of Cândido Portinari. The study seeks to explore the potential of images as a stimulus for text production, with a specific emphasis on the short story as a discursive genre. Due to its concise nature, this genre is particularly suitable for 7th-grade Elementary School students, allowing for practical application in the classroom. In its theoretical foundation, the study addresses the challenges of reading activities in the classroom, drawing on Solé (2014), Antunes (2003), Koch and Elias (2012), and Cafiero (2010). The importance of image reading is highlighted through the works of Dionísio (2011), Kleiman (2005), Santaella (2012), and Manguel (2001), who emphasize visual literacy as a crucial component of modern education. Writing activities are discussed in light of Antunes (2022), Ferrarezi Jr. and Carvalho (2015), Geraldi (2013), Beth Marcushi (2010), Rosa, Ramos and Corbari (2019), Pereira (2022), and Santos and Teixeira (2022), all of whom stress the need for pedagogical practices integrated into students’ realities. Bakhtin (2003) and Marcuschi (2008) provide the theoretical basis on discursive genres, while Costa (2014), Gotlib (2001), Moisés (2004), and Cortázar (2006) offer in-depth analyses of the short story as a discursive genre. The methodology includes a characterization of the school and a profile of the students, detailing the sequence of planned and executed activities. The final product is a Pedagogical Notebook intended for teachers, containing all the developed activities and offering a practical, ready-to-use resource to enhance the teaching of writing and image reading. Finally, as a result, the analysis of these stories produced by seventh-grade students highlighted not only the commitment of a large part of the class to the proposal of relating Cândido Portinari's painting to literary creation, but also the difficulties encountered throughout this process. It was found that several students were successful in developing coherent and creative narratives, exploring stylistic resources that enriched their texts.